Shadow education uptake among final year students in secondary schools in Ireland: Wellbeing in a high stakes context - Selina MacCoy; Delma Byrne (The Economic and Social Research Institute (ESRI), 2022)
This paper assesses the role of shadow education (SE), i.e. organised learning activities outside formal schooling, in the lives of secondary school students of different social backgrounds and in different school settings, in a high-stakes context. It draws on multilevel analysis of longitudinal Growing Up in Ireland data, alongside narratives from in-depth case study research in 10 schools. Framed within a social reproduction approach, we show how access to SE as an educational resource is socially stratified, accessible to those with greater levels of family resources, and those attending schools with higher socio-economic student intakes. SE is viewed as an investment, particularly among students with average and above average levels of prior attainment, while high attaining students are less likely to use SE. Perhaps reflecting the normalisation of SE in the Irish context, students do not directly link engagement in such tuition to their socio-emotional wellbeing.
Keywords: 330; shadow education; educational disadvantage; student voice; terminal examination; academic performance; wellbeing